2000
DOI: 10.1007/s001340000763
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatic steatosis complicating massive insulin overdose and excessive glucose administration

Abstract: Very large amounts of glucose after massive insulin overdose are potentially dangerous. Even though the fear of hypoglycemia-induced neurologic damage should be a constant preoccupation in this situation, glucose administration should be titrated on closely monitored blood glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…by day 7. 8,9 We recorded rapid onset hepatic enzyme derangement in our patient, which was seen by the second day of glucose loading. With the stabilisation of hypoglycaemia and resumption of insulin therapy from day 5, we noted gradual improvement in the liver enzymes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…by day 7. 8,9 We recorded rapid onset hepatic enzyme derangement in our patient, which was seen by the second day of glucose loading. With the stabilisation of hypoglycaemia and resumption of insulin therapy from day 5, we noted gradual improvement in the liver enzymes.…”
Section: Discussionmentioning
confidence: 62%
“…Jolliet et al also reported a similar case of rapid onset liver dysfunction and postulated that this could have been due to acute hepatic steatosis, secondary to triglyceride accumulation. 9 Tsujimoto et al showed that derangement started in 24-48 hours and recovery took more than two weeks, while the case reported by Jolliet et al showed that derangement started after day 3 with recovery in 48 hours from peak, i.e. by day 7.…”
Section: Discussionmentioning
confidence: 97%
“…Winocur [19] and Jolliet [20] reported two similar cases, in which lactic acidosis was related to an increase of blood insulin and large doses of dextrose infusion. In both cases, it was concluded that lactic acidosis was secondary to a fatty liver caused by excess supply of glucose and insulin (endogenous in the first case, and exogenous in the second).…”
Section: Discussionmentioning
confidence: 94%
“…The use of exogenous insulin permits blood glucose to be maintained in a nearphysiological range or its increase to be limited. However, it has also some drawbacks such as hypoglycemia, which can be minored by attentive bedside care, and activation of lipogenesis, with the possible harmful fatty liver [19].…”
Section: Xavier Levervementioning
confidence: 99%